CONTRIBUTION OF ACADEMIC EXPERIENCE IN A COMMUNITY MENTAL HEALTH CENTER IN NURSE TRAINING - Cínthia Verdolin Lopes; Amanda Márcia Santos Reinaldo (Universidade Federal do Paraná, 2012)
This study aimed to report the contribution of academic experience in a Community Mental Health Center to the training of the nurse. As a result, the placing of student nurses in units of the substitutive mental health network allowed the development of skills and competencies inherent to exercising the profession. Moreover, this academic experience allowed nurse training to be in agreement with the set of transformations arising from the Psychiatric Reform in policies, practices, cultural and social knowledge, and in relation to psychological suffering, within institutions and interpersonal relationships. The dialog between Nursing and the substitutive mental health services contributed to the success in the therapy offered to individuals with mental suffering, when the care model based only on the administration of technical procedures and of medication could be overcome.